Pengembangan Media Arttrace untuk Meningkatkan Keterampilan Menari Siswa SDN Karang Satria 04 - Kristiningrum Kristiningrum (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2018)
The purpose of this research is to improve students' dancing skills using ART TRACE media with TIK devices. This work of learning innovation was developed on the basis of the lack of dance skills of grade VI students and the lack of skilled teachers in learning related to the practice of dancing, the cause because the teacher does not have the background and expertise in dancing. The model used in this study is design and development (D&d) whose feasibility of learning media has been validated by material experts and media experts who are competent in their field. From the results of media validation and material validation that has been done obtained percentage from material experts by 89% and media experts by 94%. From the validation results, experts agreed that this innovation work is in the category of Excellent so that this innovation work can be said to be worth using in learning. In learning activities, his dancing skills improved nicely, this is evidenced by the learning results obtained by students. Where before using this innovation work was below KKM, with the average score of dance skills of 65.95 increased to 80.94.